Γ-Fe2O3 nanoparticles embedded in nanohydroxyapatite matrix for magnetic hyperthermia and in vitro osteoblast cell studies. Issue 8 (1st June 2020) - Ramos-Guivar, Juan A.; Morales, Marco A.; Litterst, F. Jochen
Abstract: We report an easy and low-cost method to synthesize maghemite (γ-Fe2 O3 ) nanoparticles (NPs) embedded in a nanohydroxyapatite (HAp) matrix by using the alkaline co-precipitation route without further thermal treatment. Its structural, morphological and DC and AC magnetic properties are presented in detail. The particles heat release under an AC magnetic field experiment was studied showing that by increasing particle concentrations in water up to 20 mg mL -1 the heating is improved reaching a temperature of 45 °C in ca. 10 min. The heat release is dominated by hysteresis losses and strong dipolar interactions of blocked NPs with a broad size distribution. Transmission Electron Microscopy (TEM) images show NPs with sizes between 10 and 20 nm. Furthermore, the sample was exposed to Human (Sarcoma osteogenic) SAOS-2 line-cells to study the in vitro cytotoxicity effects compared to bare γ-Fe2 O3 NPs, bulk and nano HAp. Besides, the morphology of cells, Reactive Oxygen Species (ROS) generation and cell adhesion analysis showed that the studied materials did not produce any negative effect on the shape of SAOS-2 using concentrations of 25, 75 and 125 μg mL -1 after exposure times of 6 and 24 h. Remarkably, they showed excellent biocompatibility and no toxicity effects for the tested concentrations. Thus, the proposed materials might have potential applications in magnetic hyperthermia for cancer therapy and osteoblast cells engineering.